AKTIVITAS INSEKTISIDA EKSTRAK TITHONIA DIVERSIFOLIA (HEMSL.) A GRAY (ASTERACEAE) TERHADAP ULAT DAUN KUBIS PLUTELLA XYLOSTELLA (L.) (LEPIDOPTERA: YPONOMEUTIDAE) - Firmansyah, Efrin; ., Dadang; Anwar, Ruli (Universitas Lampung, 2017)
Insecticidal activity of extracts of Tithonia diversifolia (Hemsl.) A. Gray (Asteraceae) against the diamondback moth Plutella xylostella (L.) (Lepidoptera: Yponomeutidae). The diamondback moth, Plutella xylostella (L.) (Lepidoptera: Yponomeutidae) is one of the most destructive pests on cruciferous plants. Generally farmers use synthetic insecticides to control this pest. Intensive and excessive use of insecticides can cause some undesirable effects such as resistance, resurgence, and contamination of insecticide on environment. One effort to solve the problems caused by synthetic insecticides use is by utilization of botanical materials that are potential to be used as botanical insecticides, one of them is Tithonia diversifolia (Asteraceae). The purpose of this research was to study the insecticidal activity of T. diversifolia as a botanical insecticide against P. xylostella. The leaf residual and topical application methods were used to assess the mortality effect of the extracts. Insect mortality rate was analyzed using probit analysis to obtain LC50 and LC95 values. The results showed that the flower extract had better activity on insect mortality than the leaf extract both in leaf residual and topical application treatments.